Impedance Modeling and Stability-Oriented Parameter Optimization of Isolated Dual Active Bridge-Based Two-Stage AC-DC-DC Converter - Feng, Fan; Fang, Jingyang; Manandhar, Ujjal; Gooi, Hoay Beng; Wang, Liguo (Frontiers in Energy Research, 2022)
The isolated dual active bridge (DAB)-based two-stage AC-DC-DC converters have been widely applied in grid-connected power electronics systems. However, the impedance interactions between the DAB converter and the AC-DC rectifier can cause instability problems to the two-stage converter systems. The accurate terminal impedance characteristics of the DAB converters are still not clear due to the high frequency ac conversion stage. This makes it difficult to assess the impacts of the DAB circuit parameters on the stability of the two-stage converters. To address these issues, the impedance models of the DAB converters are originally derived in this paper. Based on the developed impedance models, the stability of the DAB-based two-stage AC-DC-DC converters is analyzed. The impacts of the DAB converter circuit parameters on the stability of the two-stage AC-DC-DC converters are comprehensively revealed by the Bode and Nyquist plots. The analysis results offer instructive implications to finetune the design rules of the DAB converters. The conclusions are validated by comprehensive simulation and experimental results.